Clustering Majors for New Students at Vocational High School Muhammadiyah 3 Yogyakarta Using Fuzzy C-Means - Az-Zahra, Rifqi Rahmatika; Umar, Rusydi; Fadlil, Abdul (Universitas Muhammadiyah Malang, 2018)
The development of the era demands quality human resources. For that need to be equipped with the knowledge and skills to be ready to compete in the world of work. Vocational High School has many skills programs. Examples of skills programs in Vocational High School are Computer Network Engineering, Audio and Video Engineering, Mechanical Engineering, Building, Drawing Techniques, Motorcycle Engineering, Installation and Power Engineering, systems that can assist in the decision-making process of prospective students. The grouping system will be created using the Fuzzy C-Means method. Grouping majors using fuzzy c-means algorithm is expected to help prospective students choose majors from the many majors that exist. This is done so that prospective students do not experience difficulties in learning activities, can develop optimally and is expected to work in accordance with the expertise that has been owned, so that ultimately can improve the quality of output and outcome of vocational education. The results obtained in this study in the form of data grouped based on 3 clusters, so that prospective students can choose the majors in accordance with the selected cluster.